Enhancing HIV self-testing uptake among university students in Rwanda: the proportion, barriers, and opportunities - Ritah Mukashyaka; Gerald Kaberuka; Alain Favina; Dan Lutasingwa; Fred Mulisa; Everest Turatsinze; Ann Karanja; Deborah Kansiime; Egide Niyotwagira; Basile Ikuzo; Mark Mohan Kaggwa; Aflodis Kagaba; et al. (BMC Public Health, 2025)
Introduction University students in Rwanda are at high risk for HIV, yet they have a low uptake of HIV self-testing, which is crucial for HIV diagnosis and prevention. This study investigated their knowledge, behaviors, and perceptions towards HIV self-testing, highlighting the barriers and opportunities whose consideration is necessary for the improvement of HIV self-testing uptake in this population. Method A concurrent mixed-method design was used, and it involved 424 students from five universities across Rwanda. Quantitative data was collected through surveys, and descriptive statistics were performed. Chi-square tests were performed, and sociodemographic variables were stratified against the awareness of HIV self-testing and HIV self-testing for the past 12 months’ variables. Qualitative data was collected through in-depth interviews and focus group discussions using interview guides developed based on the Health Belief Model (HBM) framework; data was then analyzed thematically. Results The mean age was 23 (IQR: 21; 24), with 51.2% (n=214/424) females. 64.7% (n=261/424) of students had never heard of HIV self-testing, yet 37.74% (160/424) were sexually active. Among sexually active students, 17.87% were aware of HIV self-testing, but 35.82% had never used it. The reported perceived HIV self-testing barriers include high cost, unavailability of testing kits, lack of awareness, misinformation, and absence of post-test counseling. However, some HIV self-testing opportunities, like the availability of testing kits and motivating factors for university students to test, were also reported. Conclusion Although university students reported the needs and benefits of HIV self-testing, uptake remains low due to misinformation, unawareness, unavailability, and the high cost of HIV self-testing kits. Increasing awareness, availing HIVST kits, and addressing the other reported barriers to HIV self-testing, is essential for the achievement of the universal goal of HIV status awareness among university students.
Keywords: Awareness; Barriers; Benefits; HIV self-testing; Perceptions; University students; Rwanda